Distributed Arithmetic Coding - Grangetto, M.; Magli, E.; Olmo, G. (IEEE communications letters, 2007)
We propose a distributed binary arithmetic coder for Slepian-Wolf coding with decoder side information, along with a soft joint decoder. The proposed scheme provides several advantages over existing schemes, and its performance is equal to or better than that of an equivalent scheme based on turbo codes at short and medium block lengths.